INNOVATION IN BIOCOMPATIBLE MATERIALS FOR DENTAL IMPLANTS: CURRENT PERSPECTIVE AND SITUATIONS - Asaftei Victoria; Ciornei Mădălina; Țabără Eduard Lucian; Agop-Forna Doriana; Maxim Alexandra; Norina Forna (Romanian Journal of Medical and Dental Education)
Peri‐implantitis is an inflammatory disease of hard and soft tissues around osseointegrated implants, followed by a progressive damage of alveolar bone. Oral microorganisms can adhere to all types of surfaces by the production of multiple adhesive factors. Inherent properties of materials will influence not only the number of microorganisms, but also their profile and adhesion force onto the material surface. In this perspective, strategies to reduce the adhesion of pathogenic microorganisms on dental implants and their components should be investigated in modern rehabilitation concepts in implant dentistry. To date, several metallic nanoparticle films have been developed to reduce the growth of pathogenic bacteria. However, the main drawback in these approaches is the potential toxicity and accumulative effect of the metals over time. In view of biological issues and in attempt to prevent and/or treat peri‐implantitis, biomaterials as carriers of antimicrobial substances have attracted special attention for application as coatings on dental implant devices. In this review we overview currently available biomaterial systems that can be used in the field of oral implantology.